Südafrika, Eswatini, Mosambik. Komati-Kontakt: Frühe Eisenzeit und Kontakte zwischen späten Jäger-Sammler- und frühen Ackerbaukulturen im südlichen Afrika. Die Arbeiten der Jahre 2017 und 2018 - Linstädter, Jörg (e-Forschungsberichte des DAI, 2019)
The aim of the project is to study the interplay between the late hunter-gatherers of the Later Stone Age (LSA) and the early agropastoralists of the Early Iron Age (EIA) in southern Africa. For this, the catchment area of the Komati is the ideal research area, extending over South Africa, Eswatini, and Mozambique. First steps were initiated in 2017 with an excavation at the Doornkoop Iron Pig (DIP) shelter in South Africa. Research of the retrieved artefacts of the LSA layers and the overlying Iron Age deposits of the “Early Farming Societies” is still ongoing. In Mozambique, field research began in 2018 with the documentation of the shelter of Caimane and geophysical surveys, potentially revealing EIA activities.